The Dilemma "Need to Insurance" - Andreev, Yanaki (Research Papers, 2010)
The present study is the result of research into and an analysis of the recent trends on the insurance market concerning the insurable interest of the insured. The study focuses on three main aspects of this essential problem.The first part of the study looks into the fundamental need for the insured to take out insurance. This need is specified by the most popular types of insurance in the field of general insurance and in life insurance in principle.The next part dwells on the very process of taking out the types of insurance most popular on the Bulgarian insurance market, i.e. motor and fire insurance. It is assumed that the right way of taking out insurance guarantees the insured that the damages he has suffered will be adequately covered.The final part of the study mostly deals with the ever important issue of settling insurance claims (loss adjustment) in general insurance. This part focuses on the particular findings into the problems, resulting from settling insurance claims. Essential ideas and practical recommendations, concerning these problems, are put forward with the aim to improve the process of loss adjustment on the Bulgarian insurance market.